Per-oral endoscopic myotomy (POEM) training and skills evaluation tool: a pilot study - Alexander Schlachterman; Ahmed Aziz; Bader Alajlan; Samuel Han; Jorge Machicado; Mihir S. Wagh (Endoscopy International Open, 2020)
Background and study aims Hands-on training for per-oral endoscopic myotomy (POEM) in the United States is limited and without a structured curriculum or assessment tool. Training to competency in POEM is critical and POEM trainees must acquire multiple cognitive and technical skills to achieve proficiency. The aim of this study was to develop a POEM training and skills evaluation tool. Patients and methods The training protocol included initial explant porcine models followed by live human cases, proctored by a single endoscopist experienced in POEM who prospectively graded trainees for each step (“skill”) of the procedure on a 5-point scale. Procedural skills were divided into cognitive and technical skills. Acceptable passing level was considered a score ≥ 4 for each skill. Results Three trainees completed a total of 18 cases (8 cases on animal explant models and 10 human cases). Overall, cognitive skills were acquired early in training with scores of ≥ 4 achieved by ≤ 3 cases. Technical skills required more cases and direction with scores ≥ 4 in technical skills achieved by three porcine and eight human cases. Entry of the endoscope into the submucosal space and submucosal tunneling were the most challenging steps followed by myotomy. Conclusion This pilot study introduces a POEM training and skills evaluation tool for training to competency. Submucosal entry, tunneling, and myotomy were the most challenging to learn while cognitive skills were learned early in training. Evaluation of more trainees at multiple sites will be necessary to further validate the utility of this tool.